Metode Tutor Sebaya Berbantuan Whatsapp untuk Meningkatkan Hasil Uji Coba Ujian Nasional di SMK Negeri 1 Tanjungpandan - Yuli Yulianti (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
National Examination is one of the learning results assessment set by the Government, and is ruled at Minister of Education and Culture regulation Number 4 year 2018. The problem discussed in this study is the low percentage of students achieving Graduare Competence Standard/SKL 55 in the nationale examination tryout for mathematics. One of the alternatives to solve this problem is the Peer Tutoring learning method using Whatsapp Messenger application asisstance, in which the subject is grade 12 AP students of SMK Negeri 1 Tanjungpandan academic year of 2018/2019. The research method implemented is the classroom action research. The peer tutoring learning method using Whatsapp Messenger application asisstance was carried out both inside and outside the classroom by providing a smaller member whatsapp group and a classroom whatsapp group. Each small group consists of 6 people in which there were 1-2 peer tutors. Based on the results of data analysis and discussion, there was an increase at the results of the tryout of mathematics national exam tryout for grade 12 AP students after peer tutoring learning method using whatsapp messenger application asisstance was applied, with the total increase up to 50%. This fact can be inferred from the difference of the test results percentage for the first tryout and the third tryout which is from 10% to 60%, while the average score is increased from 34.96 to 60.22 by 25.26 points.